2004
DOI: 10.1007/s00477-003-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a valid model for the variogram of an isotropic spatial process

Abstract: The variogram is one of the most important tools in the assessment of spatial variability and a crucial parameter for kriging. It is widely known that an estimator for the variogram cannot be used as its representator in some contexts because of its lack of conditional semi negative definiteness. Consequently, once the variogram is estimated, a valid family must be chosen to fit an appropriate model. Under isotropy, this selection is carried out ''by eye'' from the observation of the variogram estimated curve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…We compared these scales by fuel variable and then by sample site to evaluate if fuel properties are constant across study sites. We also evaluated whether the spatial variation in fuel variables is isotropic (same in all directions) or anisotropic (directional) (Maglione and Diblasi 2004), and we addressed whether the variation is stationary (homogeneous in space). Two spatial statistics were computed to describe the spatial structure of fuel variables: Moran's I and Geary's C. Spatial analysis was performed using the geoR spatial package (Ribeiro and Diggle 2001) in R statistical computing software.…”
Section: Calculating Fuel Variabilitymentioning
confidence: 99%
“…We compared these scales by fuel variable and then by sample site to evaluate if fuel properties are constant across study sites. We also evaluated whether the spatial variation in fuel variables is isotropic (same in all directions) or anisotropic (directional) (Maglione and Diblasi 2004), and we addressed whether the variation is stationary (homogeneous in space). Two spatial statistics were computed to describe the spatial structure of fuel variables: Moran's I and Geary's C. Spatial analysis was performed using the geoR spatial package (Ribeiro and Diggle 2001) in R statistical computing software.…”
Section: Calculating Fuel Variabilitymentioning
confidence: 99%
“…Various approaches, such as computational fluid dynamics model (CFD) (Lu et al 1997;Cheng and Hu 2005) and statistical model (Kalpasanov and Kurchatova 1976;Kottegoda and Rosso 1998), have been applied to study particulate emission phenomena. Among these, the statistical model, particularly the statistical distribution model, has been proven to be a sophisticated tool for representing the useful information of pollutant data (Kumar and Jain 2010; Kim 2010; Romano et al 2004;Cassidy et al 2007;Gokhale and Khare 2007;Maglione and Diblasi 2004;Ocana-Peinado et al 2008;Babak et al 2010;Spöck and Pilz 2010). Gokhale and Khare (2007) developed a statistical distribution model to fit carbon monoxide concentrations in Delhi and the results showed that the log-logistic distribution model best fits the data at intersections, as well as roadsides.…”
Section: Introductionmentioning
confidence: 97%
“…However, there are slightly few references devoted to the testing problem. Diblasi and Bowman (2001) propose a goodness-of-fit technique to analyze spatial independence and Maglione and Diblasi (2004) extend this result in order to test if the spatial dependence structure of a data set can be explained by a certain parametric family. For multidimensional lattice data (see Besag 1974), there are several classical references on estimation and modelling.…”
Section: Introductionmentioning
confidence: 99%